PENDISTRIBUSIAN BAHAN BAKAR MINYAK NON SUBSIDI DI WILAYAH KOTA PONTIANAK KALIMANTAN BARAT - Nur Aditya E.01107014 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The background of this article would like to know the distribution of non-subsidized fuel oil in the city of Pontianak for local government service vehicles are still served in buying subsidized fuel. Formulation of the research problem is “How distribution of non-subsidized fuel for official vehicles in particular local government area of ??Pontianak city”. As for which is the goal of this study was to examine government policy to communicate the distribution, provision of resources, provide disposition and bureaucratic distribution of non-subsidized fuel at filling stations for vehicle local government offices in the city of Pontianak. Research methods here the authors use descriptive research and data collection techniques used in this study is the observation technique, interview, documentation, while the data analysis techniques the author uses descriptive qualitative technique in which data have been collected processed and analyzed qualitatively.From the analysis of the data showed that distribution of fuel subsidies in non Pontianak by the pump to the vehicle owned by the Government Office of West Kalimantan Province is still not optimal, because it is still only found a few gas stations that serve the Department charge a premium vehicle. West Kalimantan Provincial Government regulations that have been issued, by most employees are not adhered to even in the vehicle sticker bearing the ban on using premium. Parties own retail outlets still serve the Department vehicle. Therefore need to be analyzed in depth about how the government of West Kalimantan Province communicate these rules so that the gas stations and employees who use official vehicles comply with the rules that have been ditetapan, the government should also provide the human resources field, who helped oversee the distribution of non-subsidized fuel for the right target and crack down on unscrupulous employees and serving the retail outlets using the Office of premium vehicles, the government must also consider the disposition of the issued and clarify the bureaucratic system run. This thesis is intended to provide an overview of West Kalimantan Provincial Government Policies in Distribution of Fuel Subsidies in the Regional Non Pontianak. Keywords: Distribution, Non Fuel Subsidy, Sticker, Disposition, Openness Bureaucracy